2020
DOI: 10.3389/fvets.2020.00141
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Haemaphysalis Species and a Molecular Genetic Key for the Identification of Haemaphysalis of North America

Abstract: Haemaphysalis longicornis (Acari: Ixodidae), the Asian longhorned tick, is native to East Asia, but has become established in Australia and New Zealand, and more recently in the United States. In North America, there are other native Haemaphysalis species that share similar morphological characteristics and can be difficult to identify if the specimen is damaged. The goal of this study was to develop a cost-effective and rapid molecular diagnostic assay to differentiate between exotic and native Haemaphysalis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Haemaphysalis longicornis is currently distributed in 118 counties in 15 states of the United States [19]. Previously, specimens of H. longicornis were misidentified as the native rabbit tick, Haemaphysalis leporispalustris [18], resulting in a delay in an appropriate response to the incursion of this exotic tick. Haemaphysalis longicornis has most likely come to North America from East Asia [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemaphysalis longicornis is currently distributed in 118 counties in 15 states of the United States [19]. Previously, specimens of H. longicornis were misidentified as the native rabbit tick, Haemaphysalis leporispalustris [18], resulting in a delay in an appropriate response to the incursion of this exotic tick. Haemaphysalis longicornis has most likely come to North America from East Asia [24].…”
Section: Discussionmentioning
confidence: 99%
“…In North America, H. longicornis was first detected on a sheep in New Jersey in August 2017 [16]. Retrospective investigations have revealed that this tick has actually been present in the United States since 2010 [17], but it was initially misidentified as the native rabbit tick, Haemaphysalis leporispalustris (Packard, 1869) [18]. Since then, this tick has been reported in 118 counties in 15 states of the United States [19].…”
Section: Introductionmentioning
confidence: 99%
“…recorded from Saudi Arabia in Hoogstraal et al [22] were H. erinacei and H. sulcata; while in Yemen, H. leachi (presumably introduced from Africa) was reported on A. dimidiatus [21,49]. Prior to the emergence of severe fever with thrombocytopenia syndrome virus and the global spread of its vector, Haemaphysalis longicornis, molecular analyses of the genus Haemaphysalis had been relatively limited [51]. However, su cient data are available to conclude that neither the morphology nor the 16S rRNA sequences of our Haemaphysalis spp.…”
Section: Discussionmentioning
confidence: 99%
“…After the NVSL had confirmed tentative identifications and returned the subject specimens to UTK, subsequent molecular diagnostic procedures were performed to genetically confirm identifications of those ticks by amplifying 16S ribosomal DNA (rDNA) and the cytochrome c oxidase 1 (cox-1) genes, as previously described for H. longicornis confirmation identification [29][30][31]. Additionally, verified specimens of H. longicornis were screened for animal-associated pathogens.…”
Section: Methodsmentioning
confidence: 99%